2022
DOI: 10.1177/17456916221131273
|View full text |Cite
|
Sign up to set email alerts
|

Self-Prioritization Reconsidered: Scrutinizing Three Claims

Abstract: Such is the power of self-relevance, it has been argued that even arbitrary stimuli (e.g., shapes, lines, colors) with no prior personal connection are privileged during information processing following their association with the self (i.e., self-prioritization). This prioritization effect, moreover, is deemed to be stimulus driven (i.e., automatic), grounded in perception, and supported by specialized processing operations. Here, however, we scrutinize these claims and challenge this viewpoint. Although self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 117 publications
0
5
0
Order By: Relevance
“…Extending the paradigm, in Exp 2, a novel manipulation compared the SPE elicited by recordings of participants' own voices with those temporarily associated with self. Recent research suggests that temporary task goals can over-ride the prioritization of familiar self-cues such as own-face images (Cunningham et al, 2022; see also Golubickis et al, 2023), suggesting that a temporary self-association may be a stronger cue in Payne et al's task than an own-voice cue associated with other referents. However, Payne et al's (2021, Exp 3) finding that choosing the self-associated voice can increase the SPE suggests that additional links with self may boost prioritization, leading to a prediction that own-voices should elicit the strongest effects when assigned to the self label.…”
mentioning
confidence: 99%
“…Extending the paradigm, in Exp 2, a novel manipulation compared the SPE elicited by recordings of participants' own voices with those temporarily associated with self. Recent research suggests that temporary task goals can over-ride the prioritization of familiar self-cues such as own-face images (Cunningham et al, 2022; see also Golubickis et al, 2023), suggesting that a temporary self-association may be a stronger cue in Payne et al's task than an own-voice cue associated with other referents. However, Payne et al's (2021, Exp 3) finding that choosing the self-associated voice can increase the SPE suggests that additional links with self may boost prioritization, leading to a prediction that own-voices should elicit the strongest effects when assigned to the self label.…”
mentioning
confidence: 99%
“…Nevertheless, in the current study we found automatic attention capture by a self-but not close-other assigned shape that was task-irrelevant and a to-be-ignored stimulus. This finding undermines the notion that self-prioritization of newly acquired self-referential information is task-dependent (Golubickis and Macrae, 2022).…”
Section: Discussionmentioning
confidence: 56%
“…Finally, findings of the present study may provide some arguments in an ongoing debate on the topic of factors critical for the emergence of prioritization of newly acquired self-referential information. There has been a suggestion that self-prioritization is inherently contingent on tasks or goals (Golubickis and Macrae, 2022). This idea was rooted in observations from studies demonstrating that self-relevance enhanced stimulus processing solely in tasks demanding overt self vs. other differentiation (e.g., Falbén et al, 2019;Caughey et al, 2021;Woźniak and Knoblich, 2022;Żochowska et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…When participants had to decide which of two shapes flickered first, processing rates for self-associated shapes increased, relative to other-associated shapes, as a result of social association (i.e., relative to baseline). The conscious decoding of social associations was unnecessary for this effect to emerge, providing evidence against the claim that self-relatedness strictly has to be a conscious, goal-related feature in order to induce self-prioritization (e.g., Golubickis & Macrae, 2023). Instead, it supports further evidence showing that self-prioritization may emerge from the intrinsic nature of self-processing (Lee et al, 2021;Zhang et al, 2023) and unfolds across different stages of the processing hierarchy (Desebrock & Spence, 2021;Reuther & Chakravarthi, 2017;Scheller & Sui, 2022b), with early processing stages being affected in an almost automatic fashion (Alexopoulos et al, 2012;Geng & Xu, 2011;Sui et al, 2014;Yin et al, 2019).…”
Section: Social Salience Effects In Attentional Selectionprocessing L...mentioning
confidence: 99%